Jesus demodê e a construção da “ciberfé”: evidenciação da teologia líquida na apropriação da cabala - Dendasck, Carla Viana (2023)
This thesis aims to investigate the reactivation of ancient kabbalah statements as a strategy of some contemporary religious communicators, who make use of communication channels such as Youtube to explore this kind of “cyber faith” that we see propagating in social networks. In the society of the spectacle, faith communicators are among the pioneers in appropriating cyberspace to promote speeches and ideological statements, with the aim of attracting followers and expanding their respective spaces and domains of power. The communicators who acted with greater influence in Brazil until recently, fought their battles within the various aspects of Christianity, promoting new movements and religious transits. However, Orthodox Jewish rabbis began to enter this space offering knowledge about Kabbalah. They had already been signaling that the discourse of Jesus Christ, based on the proposal of love, simplicity, tolerance and friendship, was becoming, within a neoliberal society, in a way, “outmoded”. Proof of this are the various Christian religious denominations that began to incorporate elements of Judaism into their cults, promoting the recognition of Jews as “the fathers of faith”. After two years of research, it was possible to observe that this movement is expanding rapidly, gaining many followers and promoting a polarized discourse, which encourages antichrist and antichristian positions, occurring mainly through social networks. Such a movement, called “cyber faith”, is not interested in conversion to Judaism, but in the creation of an independent community, guided by its religious influencers and restricted to the environments of private platforms offering courses as a means of exercising religiosity, knowledge dogmatic and faith. Finally, it is understood that the rapid adherence to these sites that preach the knowledge of Kabbalah is the result of a church that started to practice a liquid theology, based on a blind faith as a form of dominion, which prohibited any critical argumentative capacities, especially within a scientific and technological society. As a basis for the work methodology, some channels of kabbalah promoters on Youtube were analyzed, as well as authors such as: Paveau (2022), Habermas (2015), Jung (2020), Spinoza (2021) among others